Pilot randomised controlled trial of the ENGAGER collaborative care intervention for prisoners with common mental health problems, near to and after release - Lennox, Charlotte (Pilot Feasibility Stud, 2017)
BACKGROUND: Rates of common mental health problems are much higher in prison populations, but access to primary care mental health support falls short of community equivalence. Discontinuity of care on release is the norm and is further complicated by substance use and a range of social problems, e.g. homelessness. To address these problems, we worked with criminal justice, third sector social inclusion services, health services and people with lived experiences (peer researchers), to develop a complex collaborative care intervention aimed at supporting men with common mental health problems near to and following release from prison. This paper describes an external pilot trial to test the feasibility of a full randomised controlled trial. METHODS: Eligible individuals with 4 to 16 weeks left to serve were screened to assess for common mental health problems. Participants were then randomised at a ratio of 2:1 allocation to ENGAGER plus standard care (intervention) or standard care alone (treatment as usual). Participants were followed up at 1 and 3 months’ post release. Success criteria for this pilot trial were to meet the recruitment target sample size of 60 participants, to follow up at least 50% of participants at 3 months’ post release from prison, and to deliver the ENGAGER intervention. Estimates of recruitment and retention rates and 95% confidence intervals (CIs) are reported. Descriptive analyses included summaries (percentages or means) for participant demographics, and baseline characteristics are reported. RESULTS: Recruitment target was met with 60 participants randomised in 9 months. The average retention rates were 73% at 1 month [95% CI 61 to 83] and 47% at 3 months follow-up [95% CI 35 to 59]. Ninety percent of participants allocated to the intervention successfully engaged with a practitioner before release and 70% engaged following release. CONCLUSIONS: This pilot confirms the feasibility of conducting a randomised trial for prison leavers with common mental health problems. Based on this pilot study and some minor changes to the trial design and intervention, a full two-centre randomised trial assessing the clinical and cost-effectiveness of the ENGAGER intervention is currently underway. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s40814-017-0163-6) contains supplementary material, which is available to authorized users.